Interferência de plantas daninhas em função do arranjo espacial de plantas de milho - Rios, Fabiano Aparecido (2012)
The knowledge the weed interference in crops is decisive to reach high crop yields. Besides, the constant evolution in crop management and the introduction of corn genotypes with more compact morphology and tolerance to increased plant population has led to new crop arrangements and cultural practices. The objective of the present research was to evaluate the main differences on weed-corn interactions, when the crop was sowed at row widths of 0.45 and 0.90 m, combined with "high" (54,000) and "low" (71,000 plants per hectare) corn populations. Summer-corn sowing was accomplished at November 26th, 2010, using the hybrid P30F35H. As the crop stand increased and the row width decreased, weed dry biomass was also reduced. Among the crop development variables, the most sensitive indicators to weed interference were corn stalk diameter and leaf area accumulation. Considering a maximum tolerable yield loss of 5%, the longest period of time after emergence during which weeds and crop could cohabit without crop yield (period before interference, PBI) was found for row widths of 0.45 m and "low" corn population (21 days after emergence, DAE, V6). Row widths of 0.90 m combined with "high" and "low" corn populations provided PBI of 18 and 14 DAE (V5 and V4, respectively). The combination that maximized both crop yield and susceptibility to weed interference was row widths of 0.45 m and "high" corn population, with PBI of 5 DAE (V1).